The Effect of Enviromental Pollution E-Module STEM Based (Science Technology Engineering and Mathematics) to Improve Student’s Inquiry Skills - Nurul Hidayah; Mohammad Masykuri; Murni Ramli (Jurnal Penelitian Pendidikan IPA, 2023)
STEM-based learning (Sience, technology, engineering and mathematics) is a new trend in 21st century learning. The goal of this study is to determine the effectiveness of STEM-based E-Modules to enhance learners’ inquiry skills on the subject of environmental pollution. The research population consisted of 340 students consisting of 190 students at SMP Negeri 3 Purwodadi and 150 students at SMP Negeri 2 Toroh. The research sample used 68 students at SMPN 3 Purwodadi and 68 students at SMPN 3 Toroh. The results of the N-Gain score test showed that the posttest value of the Limited Scale for the experimental class at SMP 3 Purwodadi ranged from 83.36% in the high category and 82.88% with the high category at SMPN 2 Toroh. Meanwhile, in the operational field scale test, the posttest scores ranged from 86.44% with the high category of SMPN 3 Purwodadi and 89.71% with the high category of SMPN 2 Toroh. The results of the Wilcoxon test at SMP N 2 Toroh and SMP 3 Purwodadi obtained a sig. 000 <0.05, then it can be implied that the hypothesis H0 is rejected and H1 is accepted, meaning that there is a difference in the average value of the students before being given learning using STEM-Based E-Modules and after using STEM-Based E-Modules on the subject of environmental pollution learning. The product implication is in the form of STEM-based E-Modules which are expected to increase students' inquiry skills. Suggestions for the development of a 3-dimensional Virtual Laboratory-based E-Module that integrates STEM.